FRAKSI ETANOL EKSTRAK KULIT DURIAN (Durio zibethinus L.) SEBAGAI ANTIFUNGI TERHADAP Trichophyton mentagrophytes DAN Candida albicans - Yuli Wahyu Tri Mulyani; Subur Widodo; Lisa Selviani (Fakultas MIPA Universitas Tulang Bawang Lampung, 2019)
Durian is a fruit that is in demand by the community, but during durian season environmental problems arise due to waste from skin of durian. The aimed of the study was to prove the antifungal activity of the ethanol fraction of durian skin against Trichophyton mentagrophytes and Candida albicans and to determine the active active compounds inhibiting T. mentagrophytes and C. albicans fungi. Durian skin was extracted by maceration method, then fractionated used ethanol, chloroform, and n-hexane solvents. Ethanol fraction was tested on T. mentagrophytes and C. albicans fungi used the disc method with a concentration of 10%, 20%, 40%, 60%, 80%, 100%, distilled water as a negative control, ketoconazole as a positive control. The best inhibition zone is fungi T. mentagrophytes concentration 100% ( 9.23 mm) negative control (0 mm), positive control (32.96 mm), fungi C. albicans the best inhibition zone is concentration of 100% (8.30 mm), positive control (17.17 mm) negative controls (0 mm).The ethanol fraction was screened by the Thin Layer Chromatography method and positively contained flavonoids (rf 0.7), tannins (rf 0.58), saponins (rf 0.76) and alkaloids (rf 0.64). Minimum Inhibitory Concentrations of T. mentagrophytes were 7% and C. albicans were 8%. The most effective active compound growht of T. mentagrophytes is tannins (rf 0.7) and for C. albicans is flavonoid (rf 0.6). The ethanol fraction of durian bark extract has antifungal activity against T. mentagrophytes and C. albicans. Keywords: Antifungi, Candida albicans, ethanol fraction skin of durian, Trichophytonmentagrophytes